2022
DOI: 10.36941/jesr-2022-0096
|View full text |Cite
|
Sign up to set email alerts
|

Worldwide Scientific Production on Teleworking in Scopus in Times of COVID-19

Abstract: Given the impact of COVID-19, teleworking has become an alternative work modality, so it is important to evaluate the scientific activity on the subject. Thus, the objective was to analyze the global scientific production on teleworking in times of COVID-19. Retrospective and descriptive study, whose unit of analysis was the publications on teleworking in journals indexed in the Scopus database between January 2020 and December 2021. The search was performed using the fields Article Title, Abstracts, Keywords,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
(38 reference statements)
0
2
0
4
Order By: Relevance
“…It was found that the percentage of people opting for remote work is directly proportional to the reduction in trips to workplaces. Indeed, studies showed that the restrictive measures imposed by COVID-19 led to a greater adoption of teleactivities (including teleworking), resulting in significant impacts on mobility [14][15][16]69]. Although no economic variables were included in the model, the potential teleworking percentage was included, and it is widely recognized that remote work is typically associated with a high level of education, and consequently, high incomes [57,59,62].…”
Section: Discussion Regarding the Main Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that the percentage of people opting for remote work is directly proportional to the reduction in trips to workplaces. Indeed, studies showed that the restrictive measures imposed by COVID-19 led to a greater adoption of teleactivities (including teleworking), resulting in significant impacts on mobility [14][15][16]69]. Although no economic variables were included in the model, the potential teleworking percentage was included, and it is widely recognized that remote work is typically associated with a high level of education, and consequently, high incomes [57,59,62].…”
Section: Discussion Regarding the Main Findingsmentioning
confidence: 99%
“…Even before the pandemic, the effects of teleactivities on travel behavior were already investigated, mainly taking into account substitution and complementarity [13]. However, the crisis caused by the COVID-19 pandemic changed the situation to some extent: travel restrictions imposed, as a result of the restrictive measures put in place to maintain social distancing and prevent the spread of the virus, triggered teleactivities to be implemented more intensely, thus leading to an even greater impact on mobility [14][15][16]. In this context, one of the measures suggested by the World Health Organization [2] for companies to continue operating safely was the implementation of teleworking.…”
Section: Literature Review 21 Behaviors During the Pandemicmentioning
confidence: 99%
“…Destaca-se ainda o escopo de aplicação da maioria destas análises que se concentra majoritariamente em países desenvolvidos, especialmente na Europa Ocidental e América do Norte (Mamani-Benito et al, 2022), deixando uma lacuna de conhecimento considerável a respeito dos impactos da pandemia na mobilidade urbana do Sul Global. Em virtude da rápida urbanização e altos níveis de pobreza encontrados em países africanos, latino-americanos e asiáticos, é crucial investigar se os achados observados no Norte Global podem ser generalizados para estas outras regiões.…”
Section: Justificativa E Contribuiçõesunclassified
“…De acordo com Mamani-Benito et al, (2022), mais de 995 artigos foram publicados sobre este tema entre 2020 e 2021. Cerca de ¾ desses estudos consistiram em trabalhos originais, sendo que quase 85% foram conduzidos em apenas 15 países (Estados Unidos, Índia, Reino Unido, Itália, Austrália, Indonésia, Espanha, Holanda, França, China, Canadá, Romênia, Alemanha, Japão e Malásia).…”
Section: Contexto Empíricounclassified
See 1 more Smart Citation